2007
DOI: 10.1152/jn.00621.2007
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in Sublesionally Located Neurons Following Spinal Cord Injury

Abstract: Lapointe NP, Ung R-V, Guertin PA. Plasticity in sublesionally located neurons following spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Following axonal injury, Schwann cells de-differentiate into the non-myelinating phenotype and proliferate, secreting an array of growth modulators like collagen IV, laminin and fibronectin in the surrounding domain [90]. In experimental models of SCI, Schwann cells were found to be present in the regenerated areas [91-93], which helped to regenerate the axons with various neurotrophic factors like nerve growth factor (NGF)[94], brain-derived neurotrophic factor (BDNF)[95], Neutrotrophin-3 (NT-3)[96], glial derived growth factor (GDNF)[97] and pleiotrophin (PTN, HB-GAM) [98]. In particular, Schwann cells seem to exhibit distinct motor or sensory phenotypes as per immunoreactivity towards PTN which direct regenerating axons towards the specific phenotypes [99].…”
Section: Other Cell-related Strategies For Sci With Implications To Nmentioning
confidence: 99%
“…Following axonal injury, Schwann cells de-differentiate into the non-myelinating phenotype and proliferate, secreting an array of growth modulators like collagen IV, laminin and fibronectin in the surrounding domain [90]. In experimental models of SCI, Schwann cells were found to be present in the regenerated areas [91-93], which helped to regenerate the axons with various neurotrophic factors like nerve growth factor (NGF)[94], brain-derived neurotrophic factor (BDNF)[95], Neutrotrophin-3 (NT-3)[96], glial derived growth factor (GDNF)[97] and pleiotrophin (PTN, HB-GAM) [98]. In particular, Schwann cells seem to exhibit distinct motor or sensory phenotypes as per immunoreactivity towards PTN which direct regenerating axons towards the specific phenotypes [99].…”
Section: Other Cell-related Strategies For Sci With Implications To Nmentioning
confidence: 99%
“…It is speculated that increased in local NT‐3 level may help axonal sprouting as well as strengthen the motor neurons (L3‐S4) to the sciatic nerve. The functional change is supported by the existence of a circuit of neurons in the lumbar spinal cord called the central pattern generator(CPG) 53. It has been reported that electrical stimulation can increase the expression of NT‐3 in the lumbar motor neurons and alleviate the muscle atrophy in the hindlimb, which will allow for the new treatment strategy in the injured spinal cord 54.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably related to the spontaneous recovery response. Another possible explanation for the spontaneous recovery after SCI is the increase of excitability of central pattern (CPG) neurons, which can promote locomotor movements (Lapointe et al, 2007). CPG neurons are located in lumbar segments (L1-L2 in mice, Nishimaru and Kudo, 2000), which in general correspond to sublesional spinal cord areas, where it has been shown to occur up-or down-regulation of the expression of immediate early genes (IEG), such as c-fos and nor-1, neurotrophic factors and others.…”
Section: Discussionmentioning
confidence: 99%
“…CPG neurons are located in lumbar segments (L1-L2 in mice, Nishimaru and Kudo, 2000), which in general correspond to sublesional spinal cord areas, where it has been shown to occur up-or down-regulation of the expression of immediate early genes (IEG), such as c-fos and nor-1, neurotrophic factors and others. It is known that IEG have a role on CNS development and plasticity, and therefore, they might be responsible for the increased excitability of CPG neurons after SCI (see discussion in Lapointe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%